A methodology for the distributed and collaborative management of engineering knowledge - Aziz, Hayder (Cranfield University, 2007)
The problems of collaborative engineering design and management at the conceptual stage in a large network of dissimilar enterprises was investigated. This issue in engineering design is a result of the supply chain and virtual enterprise (VE) oriented industry that demands faster time to market and accurate cost/manufacturing analysis from conception. Current tools and techniques do not completely fulfil this requirement due to a lack of coherent inter-enterprise collaboration and a dearth of manufacturing knowledge available at the concept stage. Client-server and peer to peer systems were tested for communication, as well as various techniques for knowledge management and propagation including Product Lifecycle Management (PLM) and expert systems. As a result of system testing, and extensive literature review, several novel techniques were proposed and tested to improve the coherent management of knowledge and enable inter-enterprise collaboration. The techniques were trialled on two engineering project examples. An automotive Tier-1 supplier which designs products whose components are subcontracted to a large supply chain and assembled for an Original Equipment Manufacturer (OEM) was used as a test scenario. The utility of the systems for integrating large VEs into a coherent project with unified specifications were demonstrated in a simple example, and problems associated with engineering document management overcome via re-usable, configurable, object oriented ontologies propagated throughout the VE imposing a coherent nomenclature and engineering product definition. All knowledge within the system maintains links from specification - concept - design - testing through to manufacturing stages, aiding the participating enterprises in maintaining their knowledge and experience for future projects. This potentially speeds the process of innovation by enabling companies to concentrate on value-added aspects of designs whilst ‘bread-and-butter’ expertise is reused. The second example, a manufacturer of rapid-construction steel bridges, demonstrated the manufacturing dimension of the methodology, where the early stage of design, and the generation of new concepts by reusing existing manufacturing knowledge bases was demonstrated. The solution consisted of a de-centralised super-peer net architecture to establish and maintain communications between enterprises in a VE. The enterprises are able to share knowledge in a common format and nomenclature via the building-block shareable super-ontology that can be tailored on a project by project basis, whilst maintaining the common nomenclature of the ‘super-ontology’ eliminating knowledge interpretation issues. The two-tier architecture developed as part of the solution glues together the peer-peer and super-ontologies to form a coherent system for internal knowledge management and product development as well as external virtual enterprise product development and knowledge management. In conclusion, the methodology developed for collaboration and knowledge management was shown to be more appropriate for use by smaller enterprises collaborating in a large Virtual Enterprise than PLM technology in terms of: usability, configurability, cost of system and individual control over intellectual property rights.